Donor-acceptor-donor modelled donor targets based on indoline and naphthalene diimide functionalities for efficient bulk-heterojunction devices. (January 2021) - Wagalgave, Sopan M.; Bhosale, Sheshanath V.; Puyad, Avinash L.; Chen, Jing-Yu; Jones, Lathe; Li, Jing-Liang; Gupta, Akhil; Bhosale, Sidhanath V.
Abstract: Two new organic semiconductors based on indoline and naphthalene diimide building blocks are reported for solution-processed bulk-heterojunction devices. Both materials, coded as W5 and W6, were based on the donor–acceptor–donor structural format, where indoline was used as a terminal donor and the naphthalene diimide unit was the central acceptor. Both W5 and W6 were designed to be the structural analogues where a phenyl ring was used as a π-linker in the former, and the latter comprised an additional thiophene ring. The π-linkers were induced between the donor (indoline) and acceptor (naphthalene diimide) functionalities. As a result of adding a thiophene ring in W6, its thin film demonstrated improved light-harvesting properties together with a narrower optical band gap. The photovoltaic properties were evaluated using solution-processed, bulk-heterojunction devices and W6 afforded a promising power conversion efficiency of 6.71% when tested as a donor material together with the conventional acceptor ([6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM)). The efficiency exhibited by W6 : PC71 BM is approximately 50% higher than the device based on the W5 blend (4.49%). To our knowledge, W5 and W6 are the first reported examples in the literature where indoline and naphthalene diimide units are linked together, and the optoelectronic and photovoltaic properties have been altered with the incorporation of a thiophene ring within the investigated molecular backbone. Graphical abstract: Image 1 Highlights: Donor–acceptor–donor modelled, small molecule donor semiconductors, W5 and W6 . The first connection of indoline and naphthalene diimide units to generate W5 and W6 . W5 and W6 comprised phenyl and thiophene π-linkers, respectively. Improvement of short-circuit current density and device performance with the design of W6 . PCE > 6.5% (W6 :PC71 BM) is among the leading efficiency numbers for the investigated format.